miR-181a, delivered by hypoxic PTC-secreted exosomes, inhibits DACT2 by downregulating MLL3, leading to YAP-VEGF-mediated angiogenesis - Yingxue Wang; Aiying Cen; Yuxian Yang; Huilin Ye; Jiaying Li; Shiliang Liu; Lei Zhao (Elsevier, 2021)
Papillary thyroid cancer (PTC) is the most common type of thyroid cancer, and angiogenesis plays critical roles in its recurrence and metastasis. In this study, we investigated the effects of hypoxia-induced exosomal microRNA-181 (miR-181a) from PTC on tumor growth and angiogenesis. Thyroid-cancer-related differentially expressed miR-181a was identified by microarray-based analysis in the Gene Expression Omnibus (GEO) database. We validated that miR-181a was highly expressed in PTC cells and even more so in cells cultured under hypoxic conditions, which also augmented exosome secretion from PTC cells. Exosomes extracted from PTC cells with manipulated miR-181a and mixed-lineage leukemia 3 (MLL3) were subjected to normoxic or hypoxic conditions. Human umbilical vein endothelial cells (HUVECs) were transfected with miR-181a inhibitor/mimic or small interfering RNA (siRNA)-MLL3 or treated with exosomes from hypoxic PTC cells. Hypoxic exosomal miR-181a delivery promoted proliferation and capillary-like network formation in HUVECs. Mechanistically, miR-181a targeted and inhibited MLL3. Furthermore, miR-181a downregulated DACT2 and upregulated YAP and vascular endothelial growth factor (VEGF). Further, hypoxic exosomal miR-181a induced angiogenesis and tumor growth in vivo, which was reversed by hypoxic exosomal miR-181a inhibitor. In conclusion, exosomal miR-181a from hypoxic PTC cells promotes tumor angiogenesis and growth through MLL3 and DACT2 downregulation, as well as VEGF upregulation.